Hadj Benhallou 1937-2011 - Bezzeghoud, M. (2012)
Benhallou was the first Algerian seismologist–geophysicist (Ph.D. in Geophysics, University of Algiers, 1970). Along his long teaching career as a professor of geophysics, beginning in 1961, he trained and supported many students and young researchers who came to him led by the desire to contribute to research in the field of Earth sciences.